Strength properties of lightweight foamed concrete with 30 kg/m3 steel fiber - Wong, Wai Yik (2023)
The usage of lightweight concrete is getting increase nowadays in the construction industry. Lightweight foamed concrete (LFC) is commonly found in the construction industry as it is a suitable material for thermal and sound insulation, lighter and cost-economical. However, the strength of LFC is diminished due to the low density and pore structures. According to the research, incorporating steel fiber into concrete can recover the diminished strength of lightweight foamed concrete. Hence, this study focus on the strength properties of LFC with 30 kg/m3 of steel fiber. Three types of LFC were prepared in this study, which was a trial mix of LFC (LFC-TM), a control mix of LFC (LFC-CTR), and LFC with the incorporation of 30 kg/m3 steel fiber (LFC-30SF). The LFC-CTR and LFC-30SF were cast based on the obtained optimum water-to-cement ratio from the plotted performance index curve. The fresh properties of LFC-CTR and LFC-30SF were determined from the flow table test and inverted slump test. The strength properties studied for LFC-CTR and LFC-30SF were compressive strength, splitting tensile strength and flexural strength at the curing ages of 7, 28 and 56 days. From the test results obtained, the strength of LFC was improved by adding the steel fiber into the mix. Based on the performance index, the LFC-30SF had improved compressive strength at 13.14 % and splitting tensile strength at 29.9 % compared to LFC-CTR at 56 days of curing. The improvement in flexural was not noticeable, but the effect of steel fiber was proven from the failure mode in LFC-30SF. The improvement in engineering properties of LFC was mainly due to the steel fiber reinforcement. The inclusion of steel fiber was distributed randomly throughout the concrete matrix. The orientation of steel fiber in the concrete matrix was random, which allow the bridging effect to be more significant. The steel fiber helps in bridging cracks in all directions. The stability of LFC decreased after the steel fiber was added into the mix while the workability increased. In short, incorporating steel fiber can improve the strength properties of LFC, which can increase the application of LFC in the construction industry. It was recommended to consider the low density of steel fiber in the LFC mix in future studies.